1969
DOI: 10.1111/j.1469-8137.1969.tb06468.x
|View full text |Cite
|
Sign up to set email alerts
|

APPARENT PHOTOSYNTHESIS AND LEAF CHARACTERS IN RELATION TO LEAF POSITION AND AGE, AMONG CONTRASTING LOLIUM GENOTYPES

Abstract: SUMMARYThe effect of leaf position, specific leaf weight and chlorophyll on light-saturated apparent photosynthesis, and their relationships with leaf mesophyll, among contrasting Lolium genotypes are described. Within a range of up to four fully expanded leaves on a tiller, the lower (older) leaves had greater photosynthetic activity than the upper (younger). For any particular leaf, maximum photosynthesis was attained prior to full expansion. These effects were closely related to differences in mesophyll cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…This has been found for grasses (Wilson & Cooper 1969;Garnier & Laurent 1994;Ryser & Lambers 1995;Van Arendonk et al 1997), dicot herbs (Dijkstra 1989;Meerts & Garnier 1996) and trees (Lei & Lechowicz 1990, Kloeppel & Abrams 1995. Among 34 angiosperm species, tissue dry-mass content explained interspecific variation in SLA better than leaf thickness (Shipley 1995).…”
Section: Discussionmentioning
confidence: 79%
“…This has been found for grasses (Wilson & Cooper 1969;Garnier & Laurent 1994;Ryser & Lambers 1995;Van Arendonk et al 1997), dicot herbs (Dijkstra 1989;Meerts & Garnier 1996) and trees (Lei & Lechowicz 1990, Kloeppel & Abrams 1995. Among 34 angiosperm species, tissue dry-mass content explained interspecific variation in SLA better than leaf thickness (Shipley 1995).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, the mfluence of an)-of these traits taken separately on LSM will depend on its combination with tbe otber two. This !s probably why no consistent effect of cell size on LSM bas been found: Wilson & Cooper (1969) and Dijkstra & Lambers (]989fl) found tbat low LSM coincided with large cells in different genotypes of Lolium. perenne and Plantago mafor, respectively, while Pammenter et al (1986) found tbat species with tbe bigber LSM also had larger cells.…”
Section: Leaf Specific Mass and Anatomymentioning
confidence: 99%
“…Leaf density bas seldom been measured, but sparse data suggest that leaves with a bigb LSM tend to bave a bigh proportion of vascuiar tissue and/or scierenchyma, as measured in transverse sections (Wiison, 1976a, 6;Jurik, Cbabot & Cbabot, 1982;Pammenter, Drennan & Smitb, 1986). As for cell size, while it has sometimes been shown rhat leaies witb large ceils bad a low LSM (Wilson & Cooper, 1969;Dijkstra & Lambers, 1989o), tbiy does not seem to be a general rule (e.g. Pammenter et al, 1986).…”
mentioning
confidence: 99%
“…However, in some cases changes in whole-leaf CO2 exchange have been correlated with changes in leaf anatomy. Wilson and Cooper (22)(23)(24)(25) found a negative correlation ofphotosynthetic rate with mesophyll cell size in different genotypes and experimental treatments of Lolium perenne L., although the relationship was not completely consistent. Nobel et al (15) found that changes in mesophyll cell surface area accounted for differences in CO2 exchange rates of Plectranthus parviflorus grown at several irradiances.…”
mentioning
confidence: 99%